2014
DOI: 10.4274/tjh.2014.0032
|View full text |Cite
|
Sign up to set email alerts
|

β-Thalassemia Intermedia: A Bird’s-Eye View

Abstract: Beta-thalassemia is due to a defect in the synthesis of the beta-globin chains, leading to alpha/beta imbalance, ineffective erythropoiesis, and chronic anemia. The spectrum of thalassemias is wide, with one end comprising thalassemia minor, which consists of a mild hypochromic microcytic anemia with no obvious clinical manifestations, while on the other end is thalassemia major, characterized by patients who present in their first years of life with profound anemia and regular transfusion requirements for sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
52
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 95 publications
0
52
0
Order By: Relevance
“…It has been shown that chronic hemolysis leads to NO depletion due to NO scavenging, arginine catabolism, and endogenous NO synthesis inhibition, as well as to enhanced platelet activation and increased endothelin-1 release. All of those events in turn lead to a vasculopathy characterized by endothelial dysfunction, increased vascular tone, inflammation, hypercoagulability, and, finally, vascular remodeling and destruction of the pulmonary vasculature, which ultimately results in hemolytic anemia-associated pulmonary hypertension [40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that chronic hemolysis leads to NO depletion due to NO scavenging, arginine catabolism, and endogenous NO synthesis inhibition, as well as to enhanced platelet activation and increased endothelin-1 release. All of those events in turn lead to a vasculopathy characterized by endothelial dysfunction, increased vascular tone, inflammation, hypercoagulability, and, finally, vascular remodeling and destruction of the pulmonary vasculature, which ultimately results in hemolytic anemia-associated pulmonary hypertension [40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with thalassemia intermedia with a more severe clinical picture are usually diagnosed between the ages of 2-6 years and continue their life without requiring transfusions or transfusions are rarely required. However, growth and developmental delay can be present 17,18 . In my case, thalassemia intermedia was considered, because patient was 3 years old, suff ered from developmental delay, and required transfusion.…”
Section: Discussionmentioning
confidence: 99%
“…About 1.5% of the world's population (80-90 million people) is estimated to carry the beta thalassemia trait. Th e prevalence of beta thalassemia is high in Mediterranean countries, the Middle East, Asia, Southeast China, and Far East countries as well as the North African coast and South America 17,18 . Th e frequency of beta thalassemia in Turkey was found 2.1% 16 .…”
Section: Discussionmentioning
confidence: 99%
“…34,35 Hemolytic anemia-associated pulmonary hypertension results from endothelial dysfunction, increased vascular tone, inflammation, hypercoagulability, vascular remodeling, and destruction of the pulmonary vasculature. 1,36,37 All these factors lead to elevated sFLT-1 levels among TI patients with pulmonary hypertension and those with splenectomy. Receiver operating characteristic curve analysis also showed that the cutoff value of sFLT-1 at 110 pg/mL could differentiate patients with and without pulmonary hypertension with high sensitivity and specificity.…”
Section: Discussionmentioning
confidence: 99%
“…Three main factors are responsible for the clinical sequelae of TI: ineffective erythropoiesis, chronic anemia, and iron overload. 1 Transfusional iron overload can affect heart function by directly damaging tissue through iron deposition or via ironmediated effects at other sites. The main cardiac abnormalities reported in patients with thalassemia and iron overload are left ventricular systolic and diastolic dysfunction, pulmonary hypertension, valvulopathies, arrhythmias, and pericarditis.…”
mentioning
confidence: 99%